Association of Hyponatremia on Mortality in Cryptococcal Meningitis: A Prospective Cohort. (17th June 2022) - Tugume, Lillian; Fieberg, Ann; Ssebambulidde, Kenneth; Nuwagira, Edwin; Williams, Darlisha A; Mpoza, Edward; Rutakingirwa, Morris K; Kagimu, Enoch; Kasibante, John; Nsangi, Laura; Jjunju, Samuel; Musubire, Abdu K; et al.
Abstract: Background: Sodium abnormalities are frequent in central nervous system infections and may be caused by cerebral salt wasting, syndrome of inappropriate antidiuretic hormone secretion, or medication adverse events. In cryptococcal meningitis (CM), the prevalence of baseline hyponatremia and whether hyponatremia adversely impacts survival is unknown. Methods: We conducted a secondary analysis of data from 2 randomized trials of human immunodeficiency virus–infected adult Ugandans with CM. We grouped serum sodium into 3 categories: <125, 125–129, and 130–145 mmol/L. We assessed whether baseline sodium abnormalities were associated with clinical characteristics and survival. Results: Of 816 participants with CM, 741 (91%) had a baseline sodium measurement available: 121 (16%) had grade 3–4 hyponatremia (<125 mmol/L), 194 (26%) had grade 2 hyponatremia (125–129 mmol/L), and 426 (57%) had a baseline sodium of 130–145 mmol/L. Hyponatremia (<125 mmol/L) was associated with higher initial cerebrospinal fluid (CSF) quantitative culture burden ( P < .001), higher initial CSF opening pressure ( P < .01), lower baseline Glasgow Coma Scale score ( P < .01), and a higher percentage of baseline seizures ( P = .03). Serum sodium <125 mmol/L was associated with increased 2-week mortality in unadjusted and adjusted survival analyses (adjusted hazard ratio, 1.87 [95% confidence interval, 1.26–2.79]; P < .01) compared to those with sodium 130–145 mmol/L. Conclusions: Hyponatremia is common in CM and is associated with excess mortality. A standardized management approach to correctly diagnose and correct hyponatremia in CM needs to be developed and tested. Abstract : In HIV-associated cryptococcal meningitis, baseline hyponatremia is common and is associated with higher cryptococcal culture burden, increased intracranial pressures, and altered mental status. Baseline serum sodium <125 mmol/L is associated with increased mortality through 30 days from diagnosis.